2021
DOI: 10.1111/jfbc.13748
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of Pleurotus spp. polysaccharides: A review

Abstract: Mushrooms are consumed for their nutrients and therapeutic bioactive compounds and are used medicinally in Chinese and Japanese medicine traditions since time immemorial. Members of the genus Pleurotus form a heterogeneous group of edible species with outstanding nutritional profiles rich in fiber, vitamins (thiamine, riboflavin, ascorbic acid, ergosterine, and niacin), micro and macro‐elements (phosphorus and iron), and carbohydrates. Pleurotus is one of the most diversified medicinal and edible mushrooms rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 106 publications
0
13
0
1
Order By: Relevance
“…These include high protein content, and essential amino acids enabling it to be as a substitute for meat diet; a chitin rich wall acts as a source of dietary fiber, vitamin content (B 1 , B 2 , B 12 , C, D, and E), micro and macro-elements, carbohydrates, low fat content, and almost zero cholesterol content. In relation to its composition of chemical structures, such as secondary metabolites, such as betalains and alkaloids, as well as glycoproteins and polysaccharides, Pleurotus genus is one of the most diverse edible and medicinal mushrooms [27]. Concerning their chemical composition, the mushrooms cultivated commercially are characterized by showing a similar profile of nutritional components compared to wild mushrooms.…”
Section: Macro and Micronutrientsmentioning
confidence: 99%
“…These include high protein content, and essential amino acids enabling it to be as a substitute for meat diet; a chitin rich wall acts as a source of dietary fiber, vitamin content (B 1 , B 2 , B 12 , C, D, and E), micro and macro-elements, carbohydrates, low fat content, and almost zero cholesterol content. In relation to its composition of chemical structures, such as secondary metabolites, such as betalains and alkaloids, as well as glycoproteins and polysaccharides, Pleurotus genus is one of the most diverse edible and medicinal mushrooms [27]. Concerning their chemical composition, the mushrooms cultivated commercially are characterized by showing a similar profile of nutritional components compared to wild mushrooms.…”
Section: Macro and Micronutrientsmentioning
confidence: 99%
“…isolates examined by polyacrylamide gel electrophoresis isoelectric and protein blotting, however, demonstrated that P. columbinus (Figure 1) could be regarded as a separate taxon. Despite there being many studies about the phytochemical composition of Pleurotus spp., also highlighted by recent reviews [33][34][35] there are very few studies dealing with the phytochemistry, antioxidant and antimicrobial activities of P. columbinus Quél [36,37]. Metabolomics is a new discipline which is defined as the monitoring of metabolite concentration in fungi, bacteria and plants.…”
Section: Introductionmentioning
confidence: 99%
“…[96] LDA effect size (LEfSe) was adopted to identify the taxonomic components with significant changes in gut microbiota caused by different diets, and the LDA score threshold was kept greater than 3.0. [41,97] Heat maps were generated using the "pheatmap" package in R software (version 3.3.3). The network association graph was generated by the Cytoscape (version 3.7.1) software.…”
Section: Methodsmentioning
confidence: 99%